Art Education Curriculum in Vietnam and Indonesia: Historical Perspectives on the Impact of Colonialism, Economic Reform, and Local Cultural Heritage - Kusumandyoko, Tri Cahyo; Wiratmoko, Condro; Winarno, Winarno; Martadi, Martadi; Trisakti, Trisakti (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
This article discusses commenting on the characteristics of Vietnam and Indonesia art education curricula based on colonial influences, post-socialization economic reforms, and local cultural values. Vietnamese art education was influenced by the French art program, which began in the later decades of the nineteenth century and adopted a fine arts education program. In contrast, the Indonesian art education program started in the early part of the twentieth century and reflects the Dutch style of art education that highly valued applied arts/crafts. This study explores the reciprocal relationship between economic growth and the development of art education in both countries. Through a historical-comparative approach, this study highlights how socio-economic transformations have shaped arts education policies and practices. Moreover, it assesses the contribution of art education in developing the creative economy. It suggests measures for the improvement of art education so that it can promote sustainable cultural and economic development. Based on the results of this study, it is possible to successfully combine such local features as Bale culture with foreign art education curricula to create a solid foundation for financial culture in the region via art education. Keywords: curriculum, art education, Indonesia, Vietnam